A global view on microphysical discriminations between heavier and lighter convective rainfall - Ruizi Shi; Chunsong Lu; Weixin Xu; Yali Luo (Communications Earth & Environment)
Abstract The weak linkage between heavy rainfall and strong convection hampers predictability of extreme precipitation and hinders efforts to address challenges related to global warming, especially given unclear microphysical differences between convective clouds generating disparate rain rates. Using multi-year records from spaceborne precipitation radars and cloud-permitting ensemble simulations, here we reveal microphysical distinctions between “heavier” and “lighter” rainfall in convective precipitation events worldwide, as well as their differences in environmental conditions. Results suggest that the near-surface rain rates are dictated mainly by liquid-phase processes, but the more extreme rainfall is mostly produced by vigorous mixed-phase processes combined with a rough balance between breakup and coalescence of liquid drops. With comparable convective intensity, “heavier” rainfall-producing events possess substantially higher raindrop concentration with enhanced coalescence, supported by increased environmental moisture and thicker warm-cloud layers due to enhanced water vapor channels from oceans. The “heavier” rainfall-producing weak convection is formed in the most humid environment, which compensates for the lack of vigorous mixed-phase processes leading to a maritime-like characteristic. These novel insights, along with future projections of larger-scale circulation changes by the state-of-the-art climate models, highlight the increased risk of more frequent and extreme rainfall in southern Asia and the maritime continent islands.